Bridging knowledge and practice: Prospective mathematics teachers’ analysis of student worksheet - Sulastri , Rini; Johar, Rahmah; Munzir, Said (Beta: Jurnal Tadris Matematika, 2025)
[English]: Understanding students' difficulties in solving mathematics problems is crucial for effective teaching. This study aims to determine the ability of prospective mathematics teachers to analyze students' work in solving PISA problems and identify the types of assistance recommended to overcome students' difficulties. Using a descriptive qualitative design within a case study framework, the research subjects consisted of two prospective mathematics teachers from a university in Aceh, who had good knowledge in answering PISA problems. Data was collected through written tests, interview, and documentation of analysis results for student answers. This study was conducted in two stages: (1) the subjects analyzed, assessed, and recommended assistance for students' work, and (2) the researcher evaluated the results of the analysis and the appropriateness of the assistance proposed by the subjects. The findings indicate that varying Pedagogical Content Knowledge (PCK) abilities of teachers can affect the accuracy of the analysis and the effectiveness of the recommended assistance. Subjects with high PCK can analyze students' work and suggest assistance appropriately. In contrast, subjects with low PCK only analyze and provide suggestions to overcome students' difficulties in general. This study emphasizes the importance of integrating content knowledge and pedagogy in preparing prospective teachers. [Bahasa]: Memahami kesulitan siswa dalam memecahkan masalah matematika sangat penting untuk pengajaran yang efektif. Penelitian ini bertujuan untuk mengetahui kemampuan calon guru matematika dalam menganalisis hasil kerja siswa dalam menyelesaikan soal-soal PISA, dan mengidentifikasi jenis bantuan yang disarankan untuk mengatasi kesulitan siswa. Dengan menggunakan pendekatan deskriptif kualitatif dengan jenis case study, subjek penelitian terdiri dari dua orang calon guru matematika dari salah satu universitas di Aceh, yang memiliki pengetahuan yang baik dalam menjawab soal-soal PISA. Data dikumpulkan melalui tes tertulis, wawancara, dan dokumentasi hasil analisis untuk jawaban siswa. Penelitian ini dilakukan dalam dua tahap: (1) subjek menganalisis, menilai, dan merekomendasikan bantuan untuk hasil kerja siswa; dan (2) peneliti mengevaluasi hasil analisis dan kesesuaian bantuan yang diusulkan subjek. Temuan menunjukkan bahwa kemampuan Pedagogical Content Knowledge (PCK) guru yang bervariasi dapat mempengaruhi ketepatan analisis dan efektivitas bantuan yang direkomendasikan. Subjek dengan PCK yang tinggi dapat menganalisis hasil kerja siswa dan menyarankan bantuan dengan tepat. Sebaliknya, Subjek dengan PCK yang rendah hanya menganalisis dan memberikan saran untuk mengatasi kesulitan siswa secara umum. Studi ini menekankan pentingnya mengintegrasikan pengetahuan konten dan pedagogi dalam mempersiapan calon guru.